Determining the prevalence of obesity in primary school students and eating habits in Izmir - Pelin Özilbey; Gül Ergör (Turkish Society of Public Health Specialists, 2015)
Abstract Objective: This study examined the prevalance of obesity in primary school students in Güzelbahçe, eating habits and parents' opinion about "Nutrition-Friendly School Project". Methods: This is a cross-sectional study. 549 children are taken to the study having education in primary schools in Güzelbahçe. Study was conducted in two public and two private schools between March-May 2012 in Güzelbahçe. We reached 549 students. The dependent variable is obesity conditions determined according to BMI. The independent variables are socio-demographic attributes, kind of school, food habits, physical activity, watching TV and computer usage and frequency of food consumption. In the research, a questionnaire was applied to student's parents in relation with independent variables and applied to students in relation with the food consumption. Height and weight of students were measured and BMI was calculated. Chi-square analysis and logistic regression were used for statistical analysis. OR's were calculated for factors that cause obesity. Results: Prevalence of obesity was 20% in the study. There is a significant higher obesity in boys than girls. Prevalence of obesity was significantly higher in higher education of mothers. There is no significant relationship between school type and eating habits and obesity. Most consumed food from the canteen by student; chocolate, fries and cornflakes. Most consumed drinks are milk, ayran and fruit juice. Parents of support this project 95.9% and most parents think that there will be a decrease in obesity for Project 89.1%. Conclusions: Higher education of mothers and higher monthly income is associated with obesity of children. Mothers can be given education about nutrition at home and healthy food preparation. Physical activity in children should be increased. Key Words: Obesity, BMI, primary education, eating habits, nutrition-friendly school project.